Live training versus e‐learning to teach implementation of listener response programs. Issue 2 (28th February 2018) - Geiger, Kaneen B.; LeBlanc, Linda A.; Hubik, Katie; Jenkins, Sarah R.; Carr, James E.
Abstract : Discrete‐trial teaching is an effective teaching procedure that must be implemented with high integrity to produce optimal learning. Behavioral Skills Training (BST) has proven effective for staff training; however, BST is time and labor intensive. Computer‐based instruction (CBI) programs may provide a more efficient and cost‐effective alternative to live training if the CBI program is as effective as BST in producing accurate implementation. The current study compared CBI to BST to train novice undergraduate students to conduct discrete‐trial teaching. Participants were randomly assigned to one of the two conditions and assessed prior to and after the completion of training. Results indicated that although both BST and CBI were effective at training participants to implement discrete‐trial teaching, BST was slightly but significantly more effective whereas CBI quickly created a return on the investment of product development.